The Globalization of Farmland : Theory and Empirical Evidence - Arezki, Rabah (IMF Working Papers; Working Paper ;, 2018)
This paper is the first to provide both theoretical and empirical evidence of farmland globalization whereby international investors directly acquire large tracts of agricultural land in other countries. A theoretical framework explains the geography of farmland acquisitions as a function of cross-country differences in technology, endowments, trade costs, and land governance. An empirical test of the model using global data on transnational deals shows that international farmland investments are on the aggregate likely motivated by re-exports to investor countries rather than to world markets. This contrasts with traditional foreign direct investment patterns where horizontal as opposed to vertical FDI dominates.